Analisis Future Value dan Present Value Terhadap Pertumbuhan Laba Produk Hydro Coco di PT. Sanghiang Perkasa (Kalbe Nutrional Kn7) Jalan Kima Makassar - A.Resky Elisa Putri; Meldilia N J Lenas; Ihsan Guntur (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
“Analysis of Future Value and Present Value on Profit Growth of Hydro Coco Products at PT. Sanghiang Perkasa (Kalbe Nutritional Kn7) Jalan Kima Makassar.” Supervised by Meldilianus N J Lenas and Ihsan Guntur. This study aims to analyze the impact of Future Value and Present Value on the profit growth of Hydro Coco products at PT. Sanghiang Perkasa. The research sample consists of primary data from financial reports for the 2019-2023 period, which will be analyzed using the SmartPLS analysis tool. The analysis results reveal that Future Value (FV) has a significant positive effect on profit growth, and Present Value (PV) also has a significant positive effect on profit growth. The FV and PV analyses can help the company evaluate investments by considering cash flows to optimize the profit growth of PT. Sanghiang Perkasa’s Hydro Coco products in the future.